2005
DOI: 10.1074/jbc.m501599200
|View full text |Cite
|
Sign up to set email alerts
|

Activated Mitofusin 2 Signals Mitochondrial Fusion, Interferes with Bax Activation, and Reduces Susceptibility to Radical Induced Depolarization

Abstract: Mitochondrial fusion in higher eukaryotes requires at least two essential GTPases, Mitofusin 1 and Mitofusin 2 (Mfn2). We have created an activated mutant of Mfn2, which shows increased rates of nucleotide exchange and decreased rates of hydrolysis relative to wild type Mfn2. Mitochondrial fusion is stimulated dramatically within heterokaryons expressing this mutant, demonstrating that hydrolysis is not requisite for the fusion event, and supporting a role for Mfn2 as a signaling GTPase. Although steady-state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
216
3
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(238 citation statements)
references
References 55 publications
15
216
3
1
Order By: Relevance
“…This would suggest that Mfn1 plays a more essential role in mediating fusion than Mfn2 or they may regulate fusion signaled from different pathways. While both Mfn1 and Mfn2 are important for mitochondrial fusion, a hydrolysis deficient form of Mfn2 was shown to stimulate mitochondrial fusion in cultured cells, and protected cells from apoptosis induced by staurosporine [79], which indicated additional regulatory functions for Mfn2. These suggest that apart from the fusion role, Mfn2 may also have additional functions that may impact the survival of cells.…”
Section: Mitochondrial Fusion Proteinsmentioning
confidence: 95%
See 2 more Smart Citations
“…This would suggest that Mfn1 plays a more essential role in mediating fusion than Mfn2 or they may regulate fusion signaled from different pathways. While both Mfn1 and Mfn2 are important for mitochondrial fusion, a hydrolysis deficient form of Mfn2 was shown to stimulate mitochondrial fusion in cultured cells, and protected cells from apoptosis induced by staurosporine [79], which indicated additional regulatory functions for Mfn2. These suggest that apart from the fusion role, Mfn2 may also have additional functions that may impact the survival of cells.…”
Section: Mitochondrial Fusion Proteinsmentioning
confidence: 95%
“…Fusion is thought to protect mitochondrial function by allowing rapid mixing of membranes, mitochondrial DNA and soluble contents that may be damaged by localized deficits of substrates as a result of cellular stress [35]. Recently, several studies indicated that during cell death mitochondrial fusion is inhibited and activation of the fusion machinery could slow down the rate of cell death [29,69,79]. There are, however, some very significant differences in the action of the fusion proteins in the regulation of cell death.…”
Section: Mitochondrial Fusion and Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…The notion that mitochondrial fission is a step towards death is reinforced by the ability of overexpressed pro-fusion Mfn1 and Mfn2 to block apoptosis induced by stimuli that recruit the mitochondrial pathway, perhaps by interfering with Bax activation. 56,57 An open question is why increased fission accelerates cell death. A unifying model proposed by Shore and co-workers 58 implies cristae remodelling downstream of Drp1 activation, which in turn depends on mitochondrial Ca 2 Ăž uptake induced by the BH3-only molecule BIK.…”
Section: Function Follows Form: Consequences Of Mitochondrial Shape Cmentioning
confidence: 99%
“…Continuous illumination of TMRM can trigger singlet oxygen ( 1 O 2 ) generation and thereby lead to photodynamic damage, opening of the mitochondrial permeability transition pore (PTP), and mitochondrial depolarization (11,(21)(22)(23)(24). Additionally, TMRM photobleaching during image acquisi- ORIGINAL ARTICLE tion might reduce the fluorescence signal in a Dw-independent manner.…”
Section: Relevance Of Tmrm-induced Photodamagementioning
confidence: 99%